Aplicación de un sistema acondicionador de variables para el cultivo de tomate rojo bajo invernadero mediante lógica difusa - Cañizares Sinailin, Norma Angélica (2016)
This project was aimed to design and implement an automated control by fuzzy logic of irrigation and ventilation systems for the cultivation of red tomato greenhouse, for which a review of issues related to weather conditions and their influence was held in the production of red tomato and served as a theoretical basis. In addition field trials, data analysis and graphical both ambient temperature and soil moisture, which was determined with a single sensor is sufficient for each variable to control was performed. In this project, a PLC Siemens S7-1200, CPU 1214C (AC / DC / RY) was used as the technical characteristics, this was coupled to the needs of the project also own software of this brand, TIA PORTAL, has a easy operation. The PLC receives at its inputs the conditioned signals from the sensors, processes the information and sends it to the control elements, switching and signaling connected at their outputs, resulting in the control variables. Indicators to be analyzed and contrasted, arrogated to result in better quality and higher production rate in the harvest of automated part over traditional obtained.